Evaluation of Gafchromic EBT-XD film, with comparison to EBT3 film, and application in high dose radiotherapy verification. (29th October 2015) - Palmer, Antony L; Dimitriadis, Alexis; Nisbet, Andrew; Clark, Catharine H
Abstract: There is renewed interest in film dosimetry for the verification of dose delivery of complex treatments, particularly small fields, compared to treatment planning system calculations. A new radiochromic film, Gafchromic EBT-XD, is available for high-dose treatment verification and we present the first published evaluation of its use. We evaluate the new film for MV photon dosimetry, including calibration curves, performance with single- and triple-channel dosimetry, and comparison to existing EBT3 film. In the verification of a typical 25 Gy stereotactic radiotherapy (SRS) treatment, compared to TPS planned dose distribution, excellent agreement was seen with EBT-XD using triple-channel dosimetry, in isodose overlay, maximum 1.0 mm difference over 200–2400 cGy, and gamma evaluation, mean passing rate 97% at 3% locally-normalised, 1.5 mm criteria. In comparison to EBT3, EBT-XD gave improved evaluation results for the SRS-plan, had improved calibration curve gradients at high doses, and had reduced lateral scanner effect. The dimensions of the two films are identical. The optical density of EBT-XD is lower than EBT3 for the same dose. The effective atomic number for both may be considered water-equivalent in MV radiotherapy. We have validated the use of EBT-XD for high-dose, small-field radiotherapy, for routine QC and a forthcoming multi-centre SRS dosimetry intercomparison.